Trilce, the desire of the act - Rowe, William (2022)
Although several poems of Trilce seem to indicate a horizon of utopian hope, a careful reading finds, rather, that hope is conditioned by the difficulty of accessing the act. There is no image or proposal of the act, but rather a presentation of the substratum from which the act should emerge as an ethical act. This substratum consists of the molecular time that characterizes the book in its totality and that constitutes a destruction of modern time-space. Then, the act would be preceded by a certain annulment of existing reality. The act traverses that without form; the desire of the act in Trilce includes the annulment of the separation of art and life.